2012
DOI: 10.2119/molmed.2011.00498
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Mesenchymal Stem Cells Improve Survival and Motor Function in Experimental Amyotrophic Lateral Sclerosis

Abstract: Despite some advances in the understanding of amyotrophic lateral sclerosis (ALS) pathogenesis, significant achievements in treating this disease are still lacking. Mesenchymal stromal (stem) cells (MSCs) have been shown to be effective in several models of neurological disease. To determine the effects of the intravenous injection of MSCs in an ALS mouse model during the symptomatic stage of disease, MSCs (1 × 10 6 ) were intravenously injected in mice expressing human superoxide dismutase 1 (SOD1) carrying t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
104
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 53 publications
6
104
0
1
Order By: Relevance
“…Intravenous administration of allogeneic MSCs after the onset of motor symptoms prolonged the life span of SOD-G93A mice [94]. Injected MSCs scantly homed to the CNS, but a significant reduction of accumulation of ubiquitin agglomerates and of activated astrocytes and microglia was observed in the spinal cord of MSC-treated SOD1/G93A mice, together with a significant inhibition of the excessive release of glutamate [94]. Similarly, an impact on microglial phenotype with increased percentage of ramified, resting cells and a decreased number of activated cells upon intrathecal MSC treatment after disease onset was observed by Boido and coworkers [95].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 97%
See 1 more Smart Citation
“…Intravenous administration of allogeneic MSCs after the onset of motor symptoms prolonged the life span of SOD-G93A mice [94]. Injected MSCs scantly homed to the CNS, but a significant reduction of accumulation of ubiquitin agglomerates and of activated astrocytes and microglia was observed in the spinal cord of MSC-treated SOD1/G93A mice, together with a significant inhibition of the excessive release of glutamate [94]. Similarly, an impact on microglial phenotype with increased percentage of ramified, resting cells and a decreased number of activated cells upon intrathecal MSC treatment after disease onset was observed by Boido and coworkers [95].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 97%
“…Intravenous administration of allogeneic MSCs after the onset of motor symptoms prolonged the life span of SOD-G93A mice [94]. Injected MSCs scantly homed to the CNS, but a significant reduction of accumulation of ubiquitin agglomerates and of activated astrocytes and microglia was observed in the spinal cord of MSC-treated SOD1/G93A mice, together with a significant inhibition of the excessive release of glutamate [94].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In the SOD1 animal model, injection of MSC intrathecally decreased motor neuron loss in the lumbar spinal cord, preserved motor function, and extended survival. In a recent study, MSC were injected intravenously in an ALS mouse model expressing SOD1 carrying the G93A mutation and showed to improve the survival and motor functions [81]. In the same study researches observed a reduced accumulation of ubiquitin agglomerates and of activated astrocytes and microglia in the spinal cord of treated mice and no changes in the number of choline acetyltransferase and glutamate transports type 1-possitive cells [81].…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 97%
“…In a recent study, MSC were injected intravenously in an ALS mouse model expressing SOD1 carrying the G93A mutation and showed to improve the survival and motor functions [81]. In the same study researches observed a reduced accumulation of ubiquitin agglomerates and of activated astrocytes and microglia in the spinal cord of treated mice and no changes in the number of choline acetyltransferase and glutamate transports type 1-possitive cells [81]. Mazzini et al [37], transplanted autologous bone marrow MSC into the high thoracic spinal cord in 10 ALS patients.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…This provides support to the hypothesis that the restoring effects of transplanted cells in not due to cell replacement per se but, rather, it is associated with the production and release of circulating protective factors that may act both ad the CNS and PNS levels. In fact it has been shown that implanted MSCs release a series of cytokines and chemokines with anti-inflammatory properties that could be responsible of the functional improvement of mouse models of motor neuron degenerative disorder (Bigini et al, 2011;Uccelli et al, 2012).…”
Section: Transplantation Of Msc In Experimental Amyotrophic Lateral Smentioning
confidence: 99%